Convulsions in childhood shigellosis and antimicrobial resistance patterns of shigella isolates - Öztürk, Mustafa K.; Çaksen, Hüseyin; Sümerkan, Bülent (The Turkish Journal of Pediatrics, 1996)
Drug resistance patterns of 68 shigella strains were investigated prospectively in Kayseri during a period of approximately two years. The resistance was highest with ampicillin (58.8%) followed by co-trimoxazole (50%) and ampicillin-sulbactam (13%). Only 2.8 percent of cases were resistant to gentamicin, and all serogroups were sensitive to ceftriaxone. We conclude that in children with severe shigellosis, treatment with ceftriaxone is effective and better than ampicillin and co-trimoxazole for obtaining a clinical cure. We followed 18 children who experienced convulsions associated with shigellosis. Only one child had a history of febrile convulsions, and two children had histories of convulsive disorders. The majority of the children had generalized, self-limited convulsions which lasted less than ten minutes. Due to the benign and self-limited nature of most of the convulsions, neither diagnostic procedures nor drug therapy are usually necessary. These measures should, however, be considered in complicated cases characterized by focal or prolonged seizures.